Case Analysis On Air Asia Bhd - Ahmad Kamal, Kamarul Azainiazli (2009)
This paper documents the growth of Air Asia Berhad (AAB) and the low cost carriers (LCCs) around the world and specifically in Asia Market. In introduction segment thi study will provide the background of AAB and the story behind the success of the company, it will make the reader much more clear about this company before it goes any further.